Tax Avoidance Berbasis Laba Operasi Dan Total Laba Comprehensive: Bukti Dari Asia Tenggara - Sari, Hanifah Puspita; Kusuma, Marhaendra (JCA (Jurnal Cendekia Akuntansi), 2026)
This study aims to investigate the effect of dividend payment pressure and corporate governance on tax avoidance in publicly listed companies in Southeast Asia. The data were collected from the financial statements of 3,835 companies listed in Southeast Asia during 2019–2025, including the Philippines (PSE), Singapore (SGX), Thailand (SET), Indonesia (IDX), and Malaysia (MYX), sourced from the Bloomberg Database. After excluding loss-making companies and those that did not regularly publish financial statements, the final sample consisted of 1,392 firm-years. Data were analyzed using multiple linear regression. Drawing on agency theory, the fraud triangle theory, and signaling theory, the study finds that dividend payment pressure increases tax avoidance, while strong corporate governance constrains it, with results remaining consistent in robustness tests and 2SLS endogeneity checks. The originality of this research lies in the measurement of tax avoidance, which is modified using effective tax rates based on operating income (ETR-OI) and comprehensive income (ETR-CI). This study provides a more precise measurement of tax avoidance and offers new empirical evidence from Southeast Asian companies. Keywords: Effective Tax Rate, Operating Income, Comprehensive Income, Tax Avoidance, Southeast Asia